New Route to Synthesis of Unexpected Pyridoin Derivatives: Their Structure Determination with Spectroscopic and X-Ray Methods - Cukurovali, Alaaddin (Taylor & Francis Inc, 2009)
The new 1,2,4-triazine-3-thione derivatives were obtained by a new route using a one-step process. The structure of the compounds was determined with infrared (IR), H-1 NMR, and C-13 NMR spectroscopic methods and elemental analysis. A representative x-ray crystallographic analysis of 3 was given, and its x-ray data are discussed in detail. This is a facile procedure and shorter than earlier methods.
Keywords: Cyclization; pyridoin; triazine-3-thione